Advancements in extracellular vesicle targeted therapies for rheumatoid arthritis: insights into cellular origins, current perspectives, and emerging challenges - Maryam Talebi Jouybari; Fatemeh Mojtahedi; Mahnaz Babaahmadi; Maryam Faeed; Mohammadreza Baghaban Eslaminejad; Leila Taghiyar (Stem Cell Research & Therapy)
Abstract Rheumatoid arthritis (RA) remains a challenging chronic autoimmune disorder characterized by persistent joint inflammation and damage. While modern regenerative strategies, encompassing cell/stem cell-based therapies, gene therapy, and tissue engineering, have advanced tissue repair efforts, a definitive cure for RA remains elusive. Consequently, there is growing interest in developing targeted therapies that directly address the underlying mechanisms driving RA pathogenesis, such as extracellular vesicles (EVs). These small membrane-bound particles can modulate immune responses within the inflammatory microenvironment of damaged cartilage. To launch the clinical potential of EVs, they can be isolated from various cell types through several techniques. EVs can carry various bioactive molecules and anti-inflammatory or pro-regenerative drugs, deliver them directly to the affected joints, and affect the behavior of injured cells, making them a compelling choice for targeted therapy and drug delivery in RA patients. However, there are still several challenges and limitations associated with EV-based therapy, including the absence of standardized protocols for EV isolation, characterization, and delivery. This review provides a comprehensive overview of the cellular sources of EVs in RA and delves into their therapeutic potential and the hurdles they must overcome.